Development of culturally sensitive Pain Neuroscience Education for first-generation Turkish patients with chronic pain: A modified Delphi study. (February 2019) - Orhan, Ceren; Cagnie, Barbara; Favoreel, An; Van Looveren, Eveline; Akel, Umit; Mukhtar, Naziru Bashir; De Meulemeester, Kayleigh; Pas, Roselien; Lenoir, Dorine; Meeus, Mira
Abstract: Background: Pain Neuroscience Education (PNE) has been recognized as an efficacious approach for chronic pain, but evidence for these findings have mainly been gathered in Caucasian patient populations. In recent years, it has been proposed that the treatment of pain and patient information materials should be culturally sensitive for different ethnic populations and cultures since cultural variations in pain beliefs and cognitions. Objectives: To culturally adapt PNE material for first-generation Turkish patients with chronic pain. Design: A modified Delphi study with three consecutive rounds. Method: A total of 10 participants (8 experts and 2 first-generation Turkish patients with chronic pain) were recruited for this study. Three online questionnaire rounds were conducted to synthesize the perspectives and to reach agreement on the suggested PNE materials. Results: Results on multiple-choice questions from the first round revealed that the compatibility of the visual information and the clarity of the message obtained lower scores. Examples, visual information (illustrations, pictures), and metaphors in the teaching materials and the home education leaflet were revised based on suggestions in Rounds 1 and 2. In Round 3, respondents reached an acceptable agreement level for the clinical usefulness of the PNE teaching materials and the home education material. Conclusions: Culturally sensitive PNE materials were produced for first-generation Turkish patients. Since the results of the present study only reveal perspectives of the experts, further validation of education materials may be required before they are recommended for Turkish patients in clinical practices. Highlights: Culturally sensitive PNE materials were developed for Turkish patients. Culture and gender specific changes were performed in the PNE materials. Respondents reached an acceptable agreement level for clinical usefulness. Further validation of education materials may be required.